Test load determination on composite Standard Malaysian Rubber constant viscosity 60 for earthquake isolator - Mohd Azli, Salim (Universiti Malaysia Perlis (UniMAP), 2020)
Link to publisher's homepage at http://ijneam.unimap.edu.my